Hyperglycemia during induction therapy for acute lymphoblastic leukemia is temporally linked to pegaspargase administration. Issue 7 (21st December 2021) - Pollock, Netanya I.; Flamand, Yael; Zhu, Jia; Millington, Kate; Stevenson, Kristen; Silverman, Lewis B.; Vrooman, Lynda M.; Cohen, Laurie E.
Abstract: Background: Chemotherapy regimens containing glucocorticoids and pegaspargase are associated with hyperglycemia; however, the pattern and underlying risk factors are not well characterized. We determined the pattern of hyperglycemia and associated factors in children with acute lymphoblastic leukemia (ALL) receiving glucocorticoids and pegaspargase during induction. Methods: Retrospective analysis of patients treated between 2010 and 2020 at a single institution. Pretreatment data, glucose values, and insulin regimens were abstracted from the record. Hyperglycemia was defined as two or more random glucose measurements ≥200 mg/dl. Analyses of demographic and clinical factors were conducted with logistic regression. Results: Two hundred thirteen patients, median age 6 years (range 1.0–18.9 years), 47% female, were included. The prevalence of hyperglycemia was 23% ( n = 48). Mean glucose levels peaked 3 days following administration of pegaspargase. In multivariable analysis, age ≥10 years (odds ratio [OR] 6.2, 95% confidence interval [CI]: 2.9–13.4), female sex (OR 2.7, 95% CI: 1.2–6.2), and family history of diabetes (OR 3.2, 95% CI: 1.4–7.3) were predictive of hyperglycemia. Age ≥10 years (OR 19.4, 95% CI: 5.5–68.4), family history of diabetes (OR 8.2, 95% CI: 2.7–25.3), and higher body mass index (BMI) (OR 1.8, 95% CI: 1.1–2.9) were associated with insulin treatment. Conclusions: Onset of hyperglycemia in children receiving induction chemotherapy for ALL is temporally linked to administration of pegaspargase. Older age, female sex, and family history of diabetes are predictive of hyperglycemia during induction; older age, family history of diabetes, and higher BMI are associated with insulin treatment. Frequent glucose monitoring is indicated during induction therapy for ALL.